Measures of Hearing Threshold and Temporal Processing across the Adult Lifespan - Humes, Larry E. (2009)
Psychophysical data on hearing sensitivity and various measures of supra-threshold auditory temporal processing are presented for large groups of young (18–35 y), middle-aged (40–55 y) and older (60–89 y) adults. Hearing thresholds were measured at 500, 1414 and 4000 Hz. Measures of temporal processing included gap-detection thresholds for bands of noise centered at 1000 and 3500 Hz, stimulus onset asynchronies for monaural and dichotic temporal-order identification for brief vowels, and stimulus onset/offset asynchronies for the monaural temporal masking of vowel identification. For all temporal-processing measures, the impact of high-frequency hearing loss in older adults was minimized by a combination of low-pass filtering the stimuli and use of high presentation levels. The performance of the older adults was worse than that of the young adults on all measures except gap-detection threshold at 1000 Hz. Middle-aged adults performed significantly worse than the young adults on measures of threshold sensitivity and three of the four measures of temporal-order identification, but not for any of the measures of temporal masking. Individual differences are also examined among a group of 124 older adults. Cognition and age were found to be significant predictors, although only 10–27% of the variance could be accounted for by these predictors.